Korespondensi Fonemis Bahasa Alune dan Wemale: Phonemic Correspondence in Alune and Wemale Languages - Yohanis Sanjoko; Erniati Erniati (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
This study aims to describe the linguistic situation and the phonemic correspondence formula for Alune and Wemale languages. The Alune and Wemale languages ​​are derived from the same family, the Autronesian family. Alune and Wemale languages ​​have many speakers and are spread on Seram Island, Maluku Province. The kinship of languages ​​is proven not only from the close geographical location, but also evidenced in several glossos that have kinship in the field of phonemic correspondence. The method used is descriptive qualitative method. Data collection was carried out by interviewing informant informants and then analyzed using the phonemic correspondence analysis method between the Alune language and Wemale language with the data source is two hundred basic swadesh vocabulary which will be compared between the two languages. The results of the study showed that fourteen glossos were found to have the same shape, sound and meaning in common. Alune and Wemale languages ​​show phonemic correspondence which appears regularly in the form of vowels and consonants. The phonemic correspondence formula found in Alune and Wemale languages ​​has ten phonemic correspondences, namely b~p/#-, /ø~y/#-, /ø~a/#K-, /e~a/-#, /E~e/#-, /a~u/#K-, /E~ø/-#, /p~k/#-,  /n~l/#-, /m~s/#-, dan /l~d/#-.